Dampak Penyambungan PLTM Bayang Nyalo ke Sistem 20 kV PLN ULP Painan, Sumatera Barat - Nasir, Muhammad; Kamil, Insannul; Adrianti, Adrianti; Syafdini, Riki (Universitas Sultan Ageng Tirtayasa, 2024)
The electric power distribution system will change very quickly along with the growth of the load which tends to increase every year. The increase of electricity demand must be anticipated with the addition of the number of generating plants that will integrate to the system in order to carry out continuous and optimal system operations. Before adding new generators to the system, a feasibility study will be conducted to provide optimal results using simulation of power flow studies. The connection of the Bayang Nyalo Hydro Power (BNHP) to the medium voltage 20 kV electricity system of the PLN with several operating scenarios provide significant results. The most optimal results have been obtained with scenario 2-2, which the operating voltage changed from 0.80 pu to 0.95 pu and power losses decreased from 2.04 MW to 1.67 MW. This provides a recommendation that the operating scheme of scenario 2-2 should be applied when the Bayang Nyalo Power Plant connects the PLN 20 kV system because this scenario does not require additional new investment from PLN.